2002
DOI: 10.1046/j.1365-8711.2002.05934.x
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of reported high-metallicity giant H ii regions — II. Ionizing stellar populations

Abstract: The ionizing stellar populations of 11 H II regions in the spiral galaxies: NGC 628, 925, 1232 and 1637, all of them reported to have solar or oversolar abundances according to empirical calibrations, have been analysed using stellar population synthesis models.Four of the observed regions in the sample show features which indicate the presence of a population of Wolf-Rayet (WR) stars with ages between 2.3 and 4.1 Myr. This population is sufficient to explain the emission line spectrum of the low-metallicity r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Kennicutt 1992). It is worth noting that the high metallicity H II regions within which optical Wolf-Rayet features have been detected (Bresolin & Kennicutt 2002;Castellanos et al 2002;Pindao et al 2002) are located within the disks of their host galaxies, and may suffer less extinction (and dilution) than our deeply obscured infrared star forming regions.…”
Section: Wolf-rayet Galaxiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Kennicutt 1992). It is worth noting that the high metallicity H II regions within which optical Wolf-Rayet features have been detected (Bresolin & Kennicutt 2002;Castellanos et al 2002;Pindao et al 2002) are located within the disks of their host galaxies, and may suffer less extinction (and dilution) than our deeply obscured infrared star forming regions.…”
Section: Wolf-rayet Galaxiesmentioning
confidence: 98%
“…Recent surveys of a large number of H II regions (Bresolin & Kennicutt 2002;Castellanos et al 2002;Pindao et al 2002) located in the disks of local high metallicity galaxies have revealed the presence of weak Wolf-Rayet-like features in ∼30% of the surveyed regions, which implies that Wolf-Rayet stars do in fact exist in high metallicity environments. This result confirms previous work on smaller samples Schaerer et al 2000) and high metallicity systems included in other Wolf-Rayet samples (e.g.…”
Section: Wolf-rayet Galaxiesmentioning
confidence: 99%
“…The statistical error associated with the observed emission lines is calculated using the expression σ 1 = σ c N 1/2 [1 + EW/(N∆)] 1/2 (Gonzalez-Delgado et al 1994;Castellanos et al 2002;Pérez-Montero & Díaz 2003), where σ 1 is the error in the observed line flux, σ c corresponds to the noise in the continuum near the measured emission line, N is the number of pixels used in the measurement of the line flux, EW is the line equivalent width, and ∆ is the wavelength dispersion.…”
Section: Technique To Derive the Physical Properties And Chemical Abumentioning
confidence: 99%
“…Crowther et al 2006;Fernández-Martín et al 2012;Shara et al 2012;Smith et al 2012;Kanarek et al 2015) and in nearby galaxies (e.g. Massey & Johnson 1998;Castellanos, Díaz & Terlevich 2002;Massey 2003;Eldridge & Relaño 2011;Neugent & Massey 2011;Bibby & Crowther 2012;Howarth & Walborn 2012;Neugent, Massey & Georgy 2012;Neugent, Massey & Morrell 2012;Kehrig et al 2013;Shara et al 2013;Gvaramadze et al 2014a;Massey, Neugent & Morrell 2015;Sokal et al 2015). The presence of WRs close to the nucleus of NGC 1313 was detected by Hadfield & Crowther (2007), in an H II region identified by the authors as 37.…”
Section: The Wr(s) In Regionmentioning
confidence: 90%